Food supplements' non-conformity in Europe – Poland: A case study. (November 2019) - Kowalska, Aleksandra; Bieniek, Milena; Manning, Louise
Abstract: Background: Mislabelling and substitution of ingredients in food supplements is a growing concern for regulators, businesses and consumers. Whilst there is a body of literature that has considered food and drink substitution and mislabelling, there is limited published research on the compliance of food supplements with regulatory requirements. Scope and approach: Using secondary data, the aim of this research was to identify the main factors influencing food supplements non-compliance in the European Union (EU) but with specific emphasis on Poland. The sources of data in this review were: (1) the register of pro-health foods maintained by the Chief Sanitary Inspector (GIS) in Poland; (2) unpublished data from the European Commission DG Health and Food Safety (EC DG SANTE); (3) the EU Food Fraud Network and the Administrative Assistance and Cooperation System (EU FFN & AAC) Reports; (4) the Polish Trade Inspection (IH) Report; and (5) the Rapid Alert System for Food and Feed (RASFF) Portal. Key findings and conclusions: The level of food supplements non-compliance with stated legal requirements especially mislabelling is identified in this research. Policy needs to be strengthened both at the EU level, where overarching regulatory governance can be introduced, and also in individual member states, such as Poland, where situational socio-economic factors such as health-care provision, the associated absorptive capacity of the food supplements' market and the level of ability of national institutions to institute effective regulatory and market governance influence the incidence of food supplements. Highlights: The incidence of food supplement non-conformity is a concern in Europe. Problems involve composition, nutrition, and health claims. Effective food supplement governance is essential for consumer protection.